2021
DOI: 10.1101/2021.04.29.441258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allelic variation in Class I HLA determines pre-existing memory responses to SARS-CoV-2 that shape the CD8+ T cell repertoire upon viral exposure

Abstract: Effective presentation of antigens by HLA class I molecules to CD8+ T cells is required for viral elimination and generation of long-term immunological memory. In this study, we applied a single-cell, multi-omic technology to generate the first unified ex vivo characterization of the CD8+ T cell response to SARS-CoV-2 across 4 major HLA class I alleles. We found that HLA genotype conditions key features of epitope specificity, TCR a/b sequence diversity, and the utilization of pre-existing SARS-CoV-2 reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…We observed that the PubTCR-SharedEp group is statistically enriched for carrying HLA-B*07:02, HLA-C*07:02 and HLA A*03:01, whereas the former group includes a broader set of HLAs among which HLA A*01:01 was more pronounced (Fig 5D). The enrichment of HLA-B*07:02 in the PubTCR-SharedEp group is consistent with recent work from Francis et al 15 , and these data are in agreement with their claim that CD8+ T Cell HCoV-CoV-2 cross-reactivity may be conditioned by HLA.…”
Section: Identification Of Shared and Private Immunogenic Sars-cov-2 Peptidessupporting
confidence: 92%
See 3 more Smart Citations
“…We observed that the PubTCR-SharedEp group is statistically enriched for carrying HLA-B*07:02, HLA-C*07:02 and HLA A*03:01, whereas the former group includes a broader set of HLAs among which HLA A*01:01 was more pronounced (Fig 5D). The enrichment of HLA-B*07:02 in the PubTCR-SharedEp group is consistent with recent work from Francis et al 15 , and these data are in agreement with their claim that CD8+ T Cell HCoV-CoV-2 cross-reactivity may be conditioned by HLA.…”
Section: Identification Of Shared and Private Immunogenic Sars-cov-2 Peptidessupporting
confidence: 92%
“…Rather, due to the high similarity between the cognate SARS-CoV-2 antigens and (predicted) HCoV presented peptides, we suggest it is plausible that these SARS-CoV-2 specific TCRs are crossreactive with HCoV peptides. Indeed, consistent with Francis et al, 15 who demonstrate preexisting memory CD8+ T cells to SPR* peptide in 80% of unexposed individuals, we found a set of public TCRs -which are observed in both convalescent and unexposed individualsrecognising this sCoV-2-HCoV peptide. In this light, we reveal candidate public TCRs and corresponding SARS-CoV-2 peptides with high similarity to HCoVs, which should be examined further for cross-reactive potential.…”
Section: Identification Of Shared and Private Immunogenic Sars-cov-2 Peptidessupporting
confidence: 91%
See 2 more Smart Citations
“…To delineate the T cell responses against individual HLA-I peptides in humans, we utilized a multiplexed technology combining a barcoded tetramer assay and single-cell sequencing of epitope-reactive CD8+ T cells (Figure 6E; Francis et al, 2021). Using this method, we obtained information about (1) the ex vivo frequency of CD8+ T cells reactive to each peptide in each sample; (2) the sequences of the T cell receptors (TCRs; paired a/b chains) recognizing each peptide; and (3) gene expression profiles of individual reactive CD8+ T cells.…”
Section: Out-of-frame Hla-i Peptides Elicit T Cell Responses In Humanized Hla-a2 Mice and Individuals With Covid-19mentioning
confidence: 99%